Competing Transnational Regimes under WTO Law. Issue 78 (28th February 2014) - Glinski, Carola
Against a common perception of CSR being a business concept without binding legal effect, this article discusses legitimate legal effects of private standards in public international law, using the issue of private labels as "international standards" under WTO law. WTO law shows certain openness for external transnational standards. This article argues that the references to "international standards" in the TBT Agreement can be applied for the selection between competing public or private norms that claim relevance. Thereby, the most legitimate standard for governing the problem at issue should be chosen. This is exemplified with the case of Tuna Dolphin II where the Appellate Body has emphasised the requirement of procedural legitimacy. The article argues that the requirements for legitimate standards depend on the interests at stake and that a private standard can well be more legitimate than a (competing) public standard. As the justifying effect of Article 2.5 TBT mainly interferes with economic interests, a relevant "international standard" may well consist of a representative business standard, e.g. a private label. In contrast, an international standard in the terms of Article 2.4 TBT which interferes with a democratic decision in favour of public interests such as environmental protection must reflect these public interests in a legitimate way. The article concludes that CSR can play an important role in defining legally valid justifying or minimum standards in public international law.